"Bow-tie" optimal pathway discovery analysis of sepsis hospital admissions using the Hospital Episode Statistics database in England. Issue 3 (20th September 2020) - De Oliveira, Hugo; Prodel, Martin; Lamarsalle, Ludovic; Inada-Kim, Matt; Ajayi, Kenny; Wilkins, Julia; Sekelj, Sara; Beecroft, Sue; Snow, Sally; Slater, Ruth; Orlowski, Andi
Abstract: Objective: The "Bow-tie" optimal pathway discovery analysis uses large clinical event datasets to map clinical pathways and to visualize risks (improvement opportunities) before, and outcomes after, a specific clinical event. This proof-of-concept study assesses the use of NHS Hospital Episode Statistics (HES) in England as a potential clinical event dataset for this pathway discovery analysis approach. Materials and Methods: A metaheuristic optimization algorithm was used to perform the "bow-tie" analysis on HES event log data for sepsis (ICD-10 A40/A41) in 2016. Analysis of hospital episodes across inpatient and outpatient departments was performed for the period 730 days before and 365 days after the index sepsis hospitalization event. Results: HES data captured a sepsis event for 76 523 individuals (>13 years), relating to 580 000 coded events (across 220 sepsis and non-sepsis event classes). The "bow-tie" analysis identified several diagnoses that most frequently preceded hospitalization for sepsis, in line with the expectation that sepsis most frequently occurs in vulnerable populations. A diagnosis of pneumonia (5 290 patients) and urinary tract infections (UTIs; 2 057 patients) most often preceded the sepsis event, with recurrent UTIs acting as a potential indicative risk factor for sepsis. Discussion: This proof-of-concept study demonstrates that a "bow-tie" pathway discovery analysis of the HES database can be undertaken and provides clinical insights that, with further study, could help improve the identification and management of sepsis. The algorithm can now be more widely applied to HES data to undertake targeted clinical pathway analysis across multiple healthcare conditions.